2016
DOI: 10.1161/jaha.115.002543
|View full text |Cite|
|
Sign up to set email alerts
|

Dietary α‐Linolenic Acid, Marine ω‐3 Fatty Acids, and Mortality in a Population With High Fish Consumption: Findings From the PREvención con DIeta MEDiterránea (PREDIMED) Study

Abstract: BackgroundEpidemiological evidence suggests a cardioprotective role of α‐linolenic acid (ALA), a plant‐derived ω‐3 fatty acid. It is unclear whether ALA is beneficial in a background of high marine ω‐3 fatty acids (long‐chain n‐3 polyunsaturated fatty acids) intake. In persons at high cardiovascular risk from Spain, a country in which fish consumption is customarily high, we investigated whether meeting the International Society for the Study of Fatty Acids and Lipids recommendation for dietary ALA (0.7% of to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 42 publications
1
32
0
4
Order By: Relevance
“…in heart failure 27 ), our observations can be considered supportive of a beneficial association between DPAn-3 and total mortality. Our null findings for ALA agree with some previous studies 8, 14 , but ALA levels have been associated with CVD death 26 , and ALA intake was associated with reduced total mortality in a large RCT from Spain 28 .…”
Section: Discussionsupporting
confidence: 92%
“…in heart failure 27 ), our observations can be considered supportive of a beneficial association between DPAn-3 and total mortality. Our null findings for ALA agree with some previous studies 8, 14 , but ALA levels have been associated with CVD death 26 , and ALA intake was associated with reduced total mortality in a large RCT from Spain 28 .…”
Section: Discussionsupporting
confidence: 92%
“…The double blind and randomized GISSI-HF trial showed that long-term supplementation of fish oil (1g) to heart failure patients reduced endpoints of all-causes mortality and readmission for cardiovascular complications (108). The Recent PREDIMED study supports the GISSI-HF outcome that reveals prior cardiovascular disease, relatively higher fish intake, and dietary alpha linoleic acid (one of the omega-3 fatty acid) sourced from walnuts and olive oil limit all-causes mortality, but the protection from cardiac death comes only from fish-derived long-chain omega-3 fatty acids (101). Nineteen countries comprehensive studies of free-living populations suggest that concentrations of seafood and plant-derived ω-3 fatty acids biomarkers are associated with a modestly lower incidence of fatal CHD (33).…”
Section: Failure and Success Of Pharmacological Versus Nutritional Apmentioning
confidence: 79%
“…Останнім десятиліттям проведе-но низку епідеміологічних досліджень щодо ролі здо-рового харчування й окремих нутрієнтів із первин-ної профілактики при АГ, АО, ЦД 2-го типу (OMNI HEART study, Mediterranean Diet, MUFA diet study, ATTICA registry, EPIC, SUN, PREvencion con DIeta MEDiterranea, PREDIMED study). Відомі також до-слідження щодо профілактики та сприятливих ефек-тів антигіпертензивних, антидіабетичних і анорекси-генних препаратів (KOPS, EPIC, STORM, XENDOS, RIO-EUROPA, RIO-DIABETES, [30][31][32][33][34][35][36][37][38][39][40][41].…”
Section: доказова база та дослідженняunclassified
“…Наприкінці минулого сторіччя отримано дані щодо впливу окремих нутрієнтів на рівні АТ та глі-кемії [30][31][32][33][34][35][36][37][38][39][40][41][42][68][69][70][71][72][73].Серед продуктів харчування, що містять речовини й компоненти, які поліпшують функцію ендотелію, слід назвати антоціаніни, фла-воноїдні полімери, флавоноли, ізофлавони, полі-феноли, станоли, фолієву кислоту, антиоксиданти, лютеїн, резвератрол. Метааналіз 36 досліджень із се-редньодобовим споживанням 3,7 г риб'ячого жиру демонструє вірогідне зниження АТ на 2,1/1,6 мм рт.ст.…”
Section: лікувально-профілактичне харчуванняunclassified